Dynamic interactions between the ground heat exchanger and environments in earth–air tunnel ventilation of buildings - Gan, Guohui (Elsevier, 2014)
Earth–air tunnel ventilation is an energy efficient method of preheating or cooling of supply air to abuilding. The purposes of this study are to investigate the performance of earth–air heat exchangersunder varying soil and atmosphere conditions and the interactions between the heat exchanger andenvironments. A computer program has been developed for simulation of the thermal performance of anearth–air heat exchanger for preheating and cooling of supply air, taking account of dynamic variationsof climatic, load and soil conditions. The program solves equations for coupled heat and moisture transferin soil with boundary conditions for convection, radiation and evaporation/condensation that vary withthe climate both at the soil top surface and inside the heat exchanger. The importance of dynamic inter-actions between the heat exchanger, soil and atmosphere is illustrated from the comparison of the heattransfer rates through the heat exchanger. The predicted heat transfer rate varies with operating time anddecreases along the passage of air in the heat exchanger. Neglecting the interactions would significantlyover-predict the heat transfer rate and the amount of over-prediction increases with operating time.